Polydopamine Nanoparticle Doped Nanofluid for Solar Thermal Energy Collector Efficiency Increase. (11th December 2019) - Hauser, Daniel; Steinmetz, Lukas; Balog, Sandor; Taladriz‐Blanco, Patricia; Septiadi, Dedy; Wilts, Bodo D.; Petri‐Fink, Alke; Rothen‐Rutishauser, Barbara
Abstract: Polydopamine can form black nanoparticles and has recently been gaining attention due to its extraordinary heating properties upon excitation with light. Herein, polydopamine hybrid nanoparticles are synthesized in different sizes and subsequently added to a solar fluid to analyze heating ability. The solar fluids with the differently sized hybrid polydopamine particles are compared to a solar fluid containing food coloring (i.e., micrometer‐sized soot particles, similar to India Ink) and silver nanoparticles. The hybrid polydopamine nanoparticles are found to heat more efficiently than silver nanoparticles or food coloring, respectively. In addition, no hybrid polydopamine nanoparticle deposits are found in the direct absorption solar collector in comparison to the solar fluids doped with silver nanoparticles or food coloring. Thus, this work shows that hybrid polydopamine nanoparticles are promising candidates to increase the efficiency of solar fluids. Abstract : A new dopant for solar fluids to increase heating efficiency is reported. It consists primarily of polydopamine, a material known for converting light into heat. Subjected to a solar simulator, the polydopamine nanoparticles induce a more pronounced increase in temperature of the solar fluid compared to silver nanoparticles, highlighting polydopamine nanoparticles' potential as a solar fluid dopant.